2021
DOI: 10.1002/bin.1812
|View full text |Cite
|
Sign up to set email alerts
|

Increasing physical activity and analyzing parametrically the effects on stereotypy in children with autism spectrum disorder

Abstract: A diagnosis of autism spectrum disorder (ASD) and stereotypy engagement is associated with reduced physical activity (PA). Beyond health benefits, researchers have also reported decreases in stereotypy and corresponding increases in on‐task behavior in individuals with ASD following PA. However, the duration of reported PA varies among studies examining these effects and the persistence of any effect is not well understood. Furthermore, no previous study examining these effects has reported difficulty evoking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…First, the SSPA used to determine preference among physical activities required prompting by the researchers and, therefore, it may not have been as valid as the paired‐stimulus method to measure preference. Still, these procedures have some precedent for evaluating preference among physical activities (e.g., Goldman et al, 2021; Morrison et al, 2011) and all activities were selected based on therapist or caregiver report. Second, participants had access to a limited number of physical activity options and were not taught to engage in other types of physical activity for which they may have developed preferences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, the SSPA used to determine preference among physical activities required prompting by the researchers and, therefore, it may not have been as valid as the paired‐stimulus method to measure preference. Still, these procedures have some precedent for evaluating preference among physical activities (e.g., Goldman et al, 2021; Morrison et al, 2011) and all activities were selected based on therapist or caregiver report. Second, participants had access to a limited number of physical activity options and were not taught to engage in other types of physical activity for which they may have developed preferences.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers recruited individuals who had participated in previous research which involved assessing the effects of physical activity on stereotypy (Goldman et al, 2021). Recruitment ended after these individuals were offered the opportunity to participate.…”
Section: Participants Materials and Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have suggested that the presence of ASD itself is also a variable. For example, physical activity is known to reduce stereotypies without reducing other behaviours 23 , suggesting that stereotypies and physical activity may share some mechanisms. However, physical activity can reduce cortisol 24 , 25 and stereotypies can increase cortisol as described above 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%